Bar-HRM for authenticating soursop (Annona muricata) tea - Maslin Osathanunkul (2018)
© 2018, The Author(s). Drinking soursop (Annona muricata) tea has become popular in Thailand due to recent findings about the medicinal properties of soursop tea regarding anti-cancer in particular. Consequently, numerous A. muricata tea products were found to be sold on markets and relatively expensive. It is almost impossible to identify the plant species component in the tea bag or powder products using traditional methods which are based on morphological characters. Therefore, a main objective of this study is to develop a molecular method called Bar-HRM (DNA barcoding coupled with High Resolution Melting) for authenticating A. muricata products. Three chloroplast regions including matK, rbcL and trnL were selected for in silico analyses. The findings show that rbcL is the most suitable region to be used for species identification in HRM analysis. Eleven A. muricata herbal products were purchased and tested with rbcL primers. Results from melting profile indicated that three out of eleven tested products were adulterated with other Annona species. It is believed that the Annona products are adulterated to increase the quantity and to make more profit. Notably, all of the tested products purchased from local producers were found to contain herbal species that differ from the species indicated by the seller.